The importance of evaluating performance to understand changes - Garcia Elorrio, Ezequiel (2019)
Recently, the journal published two papers that described findings on the evaluation of performance in different clinical conditions and settings but with the same goal: to give explanation to findings observed after the placement systemic interventions or established programs in real world environments. The first one from Aron et al. explores the issue of the results of fighting overtreatment in diabetic patients, resulting in undertreatment as an unintended consequence and haven’t used balancing measures to detect so during the implementation of the strategy. The second one from Hillen et al. describes the frequency of appropriate usage of medication in a vulnerable population such as the ones in residential care, which shows huge gaps in adequate use. The clinical situations described in the two studies are not the main point to comment on. The case I like to highlight is the importance of evaluating performance to detect opportunities for improvement. Both studies take profit from the retrospective review of administrative databases usually available in mature health systems as frequently observed in developed countries. This is huge asset and is a cornerstone of health services research, what constitutes the base for further research to confirm or reject hypothesis to and develop solutions in reaction to problems.